Balon Raksasa Paus Pink Dengan Pesan Ekologis - Putra Adnyana, Ida Bagus (Jurnal Pendidikan Seni Rupa Undiksha, 2025)
Abstract The installation of the giant whale sculpture by Arkiv Vilmansa is a creative expression that captures public attention and becomes an esthetic discourse. This work, also represented by limited-edition art toys, needs to be examined deeply to understand its creative process, meaning, and implications for society and the environment. This research uses a qualitative approach by collecting data through literature studies and in-depth interviews with Arkiv Vilmansa, exhibition curators, and the audience. The pink whale installation in Teluk Jimbaran, Bali, not only attracts attention but also encourages the community to think about their connection with nature and environmental responsibility. This work can be seen as an example of happening art, involving direct community participation. The use of plastic as the primary material creates a paradox that draws attention and strengthens the environmental message. This study aims to examine public response and the economic implications triggered by the artist's popularity, as well as to understand the esthetics and cultural messages conveyed through Arkiv Vilmansa's work. Keywords: art toys, pink whale, paradox Abstrak Karya instalasi patung paus raksasa oleh Arkiv Vilmansa merupakan artikulasi gagasan kreatif yang menarik perhatian khalayak dan menjadi wacana estetik. Patung ini, yang juga diwakili oleh art toys edisi terbatas, perlu dikaji lebih dalam untuk memahami proses kreatif, maknanya, dan implikasinya terhadap masyarakat dan lingkungan.Penelitian ini menggunakan pendekatan kualitatif dengan mengumpulkan data melalui studi literatur dan wawancara mendalam dengan Arkiv Vilmansa, kurator pameran, dan audiens. Instalasi paus pink di Teluk Jimbaran, Bali, tidak hanya menarik perhatian tetapi juga mengajak masyarakat untuk berpikir tentang keterhubungan mereka dengan alam dan tanggung jawab lingkungan. Karya ini dapat dilihat sebagai contoh happening art, melibatkan partisipasi langsung masyarakat. Penggunaan plastik sebagai material utama menciptakan paradoks yang menarik perhatian dan memperkuat pesan lingkungan. Penelitian ini bertujuan untuk mengkaji respon masyarakat dan implikasi ekonomi yang dipicu oleh popularitas seniman, serta memahami estetika dan pesan budaya yang disampaikan melalui karya Arkiv Vilmansa. Kata kunci: art toys, paus pink, paradoks